The Future of Macroeconomic Policy in the European Union - Christopher Allsopp (Bank of England, External Monetary Policy Committee Unit, 2002)
This paper is the text of the key-note speech on macroeconomics given by Christopher Allsopp at the 75th Anniversary Symposium of the Austrian Institute of Economic Research (WIFO) in Vienna on January 23rd 2002. It discusses the role of the European Central Bank, coordination issues between monetary and fiscal policy, and the effects of the interaction of the Stability and Growth Pact with labour market issues, especially on the processes of adjustment between countries in the euro area.
Keywords: 330